2022
DOI: 10.1093/ibd/izac228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biologic Agents on the Immune Response Induced by the Additional Dose of SARS-CoV-2 Vaccine in Inflammatory Bowel Disease Patients

Abstract: Lay Summary The immusne response to the vaccine against SARS-CoV-2 is altered in patients with inflammatory bowel disease using biological agents, and so we should ensure effective immunization in these patients by prioritizing those receiving anti-tumor necrosis factor agents in the indication of new doses or booster doses of the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Although surprisingly few patients actually got SARS-CoV-2 Omicron variant infection during the local outbreak, the vaccination coverage of Chinese patients with IBD is of concern. Only 51.2% of patients with IBD enrolled in our study had been vaccinated, whereas vaccination rates in other countries were above 60% and even up to 95% (7,10,11). Our investigation indicated that women and patients with CD and relatively severe disease status were more reluctant to be vaccinated-possibly because they worried that this might aggravate their condition, which mirrors the findings of similar studies in other countries (5,10,12).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although surprisingly few patients actually got SARS-CoV-2 Omicron variant infection during the local outbreak, the vaccination coverage of Chinese patients with IBD is of concern. Only 51.2% of patients with IBD enrolled in our study had been vaccinated, whereas vaccination rates in other countries were above 60% and even up to 95% (7,10,11). Our investigation indicated that women and patients with CD and relatively severe disease status were more reluctant to be vaccinated-possibly because they worried that this might aggravate their condition, which mirrors the findings of similar studies in other countries (5,10,12).…”
Section: Discussionsupporting
confidence: 78%
“…Major IBD societies recommend the vaccination of patients with IBD at the earliest possible stage for better protection (4,5). In practice, not all IBD clinicians suggest vaccination during the active disease stage or immunosuppressive situation, and a number of patients with IBD still hesitate to be vaccinated for various reasons, leading to suboptimal vaccination coverage (6,7). To date, there existed a limited number of documented cases of SARS-CoV-2 infection in patients with IBD on a global scale, with only one case of infection reported locally during this local Omicron wave.…”
Section: Introductionmentioning
confidence: 99%
“…Following an initial screening of 864 articles, 725 were excluded. After browsing the full texts, 32 studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ] were ultimately included in the meta-analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patientinnen und Patienten mit immunsuppressiver Therapie, Biologika oder small molecule-Therapien haben ein Risiko eines reduzierten Impfansprechens 89 90 91 . In einer Multicenter-Studie mit 483 Patientinnen und Patienten zeigte sich nach nur zwei Impfungen gegen SARS-CoV-2 eine signifikant verminderte Antikörperbildung unter Behandlung mit Infliximab, Infliximab und Azathioprin, sowie Thiopurin-Monotherapie, wenn für das Alter adjustiert wurde, für Tofacitinib hingegen nur vor der Adjustierung 92 .…”
Section: Leitlinie – Kapitel 5: Impfungenunclassified